Fabrication and evaluation of silica embedded and zerovalent iron composited biochars for arsenate removal from water. (November 2020) - Ahmad, Munir; Usman, Adel R.A.; Hussain, Qaiser; Al-Farraj, Abdullah S.F.; Tsang, Yiu Fai; Bundschuh, Jochen; Al-Wabel, Mohammad I.
Abstract: Waste date palm-derived biochar (DPBC) was modified with nano-zerovalent iron (BC-ZVI) and silica (BC-SiO2 ) through mechanochemical treatments and evaluated for arsenate (As(V)) removal from water. The feedstock and synthesized adsorbents were characterized through proximate, ultimate, and chemical analyses for structural, surface, and mineralogical compositions. BC-ZVI demonstrated the highest surface area and contents of C, N, and H. A pH range of 2–6 was optimum for BC-ZVI (100% removal), 3–6 for DPBC (89% removal), and 4–6 for BC-SiO2 (18% removal). Co-occurring PO4 3− and SO4 2− ions showed up to 100% reduction, while NO3 − and Cl − ions resulted in up to 26% reduction in As(V) removal. Fitness of the Langmuir, Freundlich and Redlich-Peterson isotherms to As(V) adsorption data suggested that both mono- and multi-layer adsorption processes occurred. BC-ZVI showed superior performance by demonstrating the highest Langmuir maximum adsorption capacity (26.52 mg g −1 ), followed by DPBC, BC-SiO2, and commercial activated carbon (AC) (7.33, 5.22, and 3.28 mg g −1, respectively). Blockage of pores with silica particles in BC-SiO2 resulted in lower As(V) removal than that of DPBC. Pseudo-second-order kinetic model fitted well with the As(V) adsorption data ( R 2  = 0.99), while the Elovich, intraparticle diffusion, and power function models showed a moderate fitness ( R 2  = 0.53–0.93). The dynamics of As(V) adsorption onto the tested adsorbents exhibited the highest adsorption rates for BC-ZVI. As(V) adsorption onto the tested adsorbents was confirmed through post-adsorption FTIR, SEM-EDS, and XRD analyses. Adsorption of As(V) onto DPBC, BC-SiO2, and AC followed electrostatic interactions, surface complexation, and intraparticle diffusion, whereas, these mechanisms were further abetted by the higher surface area, nano-sized structure, and redox reactions of BC-ZVI. Graphical abstract: Image 1 Highlights: Biochar (DPBC) composites with ZVI (BC-ZVI) and silica (BC-SiO2 ) were synthesized. As(V) removal by BC-ZVI was 5–7 folds higher than DPBC and activated carbon. BC-ZVI efficiently removed As(V) from aqueous solution under a wide pH range (2–6). Electrostatic interactions, surface complexation and diffusion were sorption mechanisms. Redox reactions were responsible for higher As(V) removal through BC-ZVI.